Answer:
x = 3 ± 5
![√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/2tk9nnsgx1ipwtsdiozl197sxl4yier48u.png)
Explanation:
x² - 6x - 41 = 0 ( add 41 to both sides )
x² - 6x = 41
to complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(- 3)x + 9 = 41 + 9
(x - 3)² = 50 ( take square root of both sides )
x - 3 = ±
= ± 5
( add 3 to both sides )
x = 3 ± 5
![√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/2tk9nnsgx1ipwtsdiozl197sxl4yier48u.png)